Integrating geographic information system and 3D virtual reality for optimized modeling of large-scale photovoltaic wind hybrid system: A case study in Dakhla City, Morocco - Elmostafa Achbab; Rachid Lambarki; Hassan Rhinane; Dennoun Saifaoui (Energy Geoscience)
This research pioneers the integration of geographic information systems (GIS) and 3D modeling within a virtual reality (VR) framework to assess the viability and planning of a 20 MW hybrid wind-solar-photovoltaic (PV) system connected to the local grid. The study focuses on Dakhla, Morocco, a region with vast untapped renewable energy potential. By leveraging GIS, we are innovatively analyzing geographical and environmental factors that influence optimal site selection and system design. The incorporation of VR technologies offers an unprecedented level of realism and immersion, allowing stakeholders to virtually experience the project's impact and design in a dynamic, interactive environment. This novel methodology includes extensive data collection, advanced modeling, and simulations, ensuring that the hybrid system is precisely tailored to the unique climatic and environmental conditions of Dakhla. Our analysis reveals that the region possesses a photovoltaic solar potential of approximately 2400 kWh/m2 per year, with an average annual wind power density of about 434 W/m2 at an 80-meter hub height. Productivity simulations indicate that the 20 MW hybrid system could generate approximately 60 GWh of energy per year and 1369 GWh over its 25-year lifespan. To validate these findings, we employed the System Advisor Model (SAM) software and the Global Solar Photovoltaic Atlas platform. This comprehensive and interdisciplinary approach not only provides a robust assessment of the system's feasibility but also offers valuable insights into its potential socio-economic and environmental impact.